Lockdown measures for COVID-19 outbreak and variation in physical activity in patients with heart failure and cardiac implantable devices. (December 2021) - Cunha, Pedro Silva; Laranjo, Sérgio; Lourenço, André; Rodrigues, Lourenço; Cardoso, Isabel; Portugal, Guilherme; Valente, Bruno; Delgado, Ana Sofia; Ferreira, Rui Cruz; Abreu, Ana; Oliveira, Mário Martins
Abstract: Aims: The present study analysed the patterns of physical activity pre-, during and post-lockdown measures for COVID-19 pandemic in patients with chronic heart failure (CHF) and cardiac implantable electronic devices (CIED) under remote monitoring (RM), and assessed the physical activity patterns during these periods. Methods: The raw data from 95 patients with CHF (age 67, 7 ± 15, 1 years, 71, 5% male) corresponding to 2238 RM transmissions of the Medtronic Carelink™ network platform was obtained. The physical exercise profiles and the impact of the lockdown measures on the physical behaviour during and after the measures were analysed. According to the level of activity duration in the pre-lockdown, lockdown and post-lockdown periods, the patterns of behaviour were identified (non-recoverees, incomplete recoverees, recoverees and full-recoverees). Conclusion: RM of CHF patients with CIED using the Carelink™ network is useful for close follow-up and identification of heart failure risk status variations. After relieving the confinement measures there were two groups of patients that did not recover the previous physical activity levels. Physical inactivity in patients with CHF can have a significant impact on outcomes.